Digital Transformation in Public Governance: A Narrative Review of Information Systems for Strategic Communication - Febriana, Ajeng Iva Dwi (Sinergi International Journal of Communication Sciences, 2025)
This study employs a narrative review approach to examine how information systems reshape strategic communication management within public institutions worldwide. Specifically, it investigates how such systems contribute to efficiency, transparency, accountability, and citizen engagement while identifying key barriers that hinder their full potential. Literature was systematically gathered from major databases including Scopus, Web of Science, PubMed, and Google Scholar, using targeted keywords such as “Information Systems,” “Strategic Communication,” “Public Institutions,” “E-Government,” “Transparency,” and “Accountability.” Studies meeting inclusion criteria consisted of peer-reviewed research with methodological clarity, focusing on outcomes relevant to public communication. Findings reveal that information systems streamline internal communication, improve productivity, and foster transparency through open data portals, enhancing trust and accountability. Platforms for e-participation and online feedback have strengthened stakeholder involvement, though effectiveness varies by region due to infrastructural, cultural, and political factors. Leadership style, human resource capacity, and organizational culture were identified as key determinants of successful adoption. Comparative evidence highlights the disparity between developed and developing regions, underscoring the importance of context-specific strategies. Despite these advances, barriers such as inadequate infrastructure, resistance to change, and limited digital literacy persist. Addressing these challenges requires investment in infrastructure, capacity-building, and supportive policy frameworks. Future research should broaden geographic representation, incorporate qualitative and longitudinal studies, and explore the role of emerging technologies. These steps are crucial for leveraging information systems to achieve more inclusive and transparent public governance.